Tuning the length/width aspect ratio of epitaxial unidirectional silicide nanowires on Si(110)-16 × 2 surfaces. (28th September 2020) - Mahato, J C; Das, Debolina; Das, P; Chini, T K; Dev, B N
Abstract: The reactive deposition epitaxy growth of self-organized cobalt silicide nanowires (NWs) on clean Si(110) surfaces has been investigated by in situ scanning tunneling microscopy (STM) and scanning tunneling spectroscopy (STS) as well as by scanning electron microscopy (SEM). Half a monolayer of cobalt was deposited on the Si(110) surfaces at ∼600 °C substrate temperature. Following cobalt deposition, the substrates have been annealed for different durations. Cobalt forms aligned cobalt disilicide nanowires upon reaction with the silicon substrate, following the twofold substrate symmetry. With increasing duration of annealing, the NWs have been found to grow with larger aspect ratio (length/width), eventually producing narrower NWs. These self-organized unidirectional NWs of sub-hundred nanometer width and ∼4–7 nm height produce a Schottky barrier with the silicon substrate and are expected to find applications in nanoelectronic devices.